Compensation and Work Motivation in Employee Performance at CV. Lucky: Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan di CV. Lucky - Saputra , Marchelino Tryas; Kusuma, Kumara Adji (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Employee performance is essential for organizational success, with compensation recognized as a significant influencing factor. Specific Background: While compensation's role is well-documented, the moderating effect of motivation in this context remains insufficiently explored. Knowledge Gap: This study seeks to fill this gap by investigating how motivation influences the relationship between compensation and employee performance. Aims: The research examines the impact of compensation on performance and how motivation moderates this relationship among 85 employees at CV Lucky. Results: Using Moderated Regression Analysis, the findings indicate a significant positive relationship between compensation and employee performance, suggesting that improved compensation enhances performance. Furthermore, better compensation correlates with increased motivation, which in turn positively affects performance. Novelty: This study highlights the moderating role of work motivation, suggesting that enhancing motivation can strengthen the impact of compensation on performance. Implications: The results emphasize the importance of effective compensation strategies that boost both performance and employee motivation, ultimately fostering organizational success. Highlights : Significant positive relationship between compensation and employee performance. Work motivation amplifies the impact of compensation on performance. Effective compensation strategies enhance both employee motivation and organizational success. Keywords: Compensation, Employee Performance, Work Motivation, Moderation, Organizational Success